PENGARUH MODAL DAN TOTAL ASET TERHADAP PEROLEHAN SISA HASIL USAHA PADA KOPERASI WANITA PUSPITA KENCANA - Rima Mardiana Putri Permatasari; Ustadus Sholihin; Heru Sutapa; Bima Alamsyah (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
Cooperatives are business entities that support the country's economy with the principle of kinship and prioritize common interests and mutual cooperation in general and can advance the prosperity of its members in particular. This study aims to determine and analyze the effect of capital and total assets on the acquisition of the remaining proceeds of the Ngadirejo Women's Puspita Kencana Cooperative in Kediri City. The object of the research used was the Ngadirejo Women's Puspita Kencana Cooperative in Kediri City, 2013-2017. The sample used in this study is the last 5 years of financial report data so that the data taken is 60 data. This type of research is quantitative research. The data analysis technique used in this study is multiple linear regression analysis using the classic assumption test first, coefficient of determination, F test and t test with SPSS tools (Statistical Product and Service Solution). The results of the research based on the F test show that capital (X1) and total assets (X2) have a positive and significant effect on the acquisition of operating income (Y).